Correlation of serum Omentin-1 levels with Diabetic peripheral neuropathy in Type-2 diabetes mellitus patients - Muhammad Sameer Hanif, Amina Nadeem, Tallat Naureen, Kamil Asghar Imam, Sidra Aslam, Muhammad Kaleem (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To establish correlation of serum omentin-I with diabetic peripheral neuropathy in type-2 diabetes mellitus (T2DM). Methods: The study was conducted at the Physiology Department, Army Medical College in collaboration with Pak Emirates Military Hospital, Rawalpindi from January 2019 to December 2019. Total 90 participants were recruited by non-probability purposive technique and were divided into three groups of 30 each. Group-I, Group-II and group-III consisted of healthy, T2DM individuals without diabetic peripheral neuropathy (DPN) and T2DM participants with DPN respectively. DPN was assessed by Michigan Neuropathy Screening Instrument (MNSI). Serum omentin-I levels were determined by enzyme-linked immunosorbent assay (ELISA). Results: Fasting blood glucose (FBG) levels and glycated hemoglobin (HbA1c) were considerably lower in group-I as compared to in group-II and group-III. There was a significant difference of body mass index (BMI) between the groups, but the difference between group-I and group-II as well as between group-II and group-III was not significant. There was observed a statistically significant difference of mean serum omentin-1 levels within all three groups with p-value < 0.0001 with highest levels in Group-I and lowest in Group-III. Serum omentin-I levels were negatively correlated with T2DM, T2DM induced DPN, HbA1c, BSF and BMI. Conclusion: Serum omentin-I is an anti-inflammatory & anti-oxidant adipocytokine in T2DM and has potential protective beneficial role in preventing DPN. Keywords: Omentin-1, Diabetic peripheral neuropathy, Type-2 diabetes mellitus